If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2(sin(x)) = 9 + -6(sin(x)) Multiply ins * x 5 + -2(insx) = 9 + -6(sin(x)) Multiply ins * x 5 + -2insx = 9 + -6(insx) Solving 5 + -2insx = 9 + -6insx Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '6insx' to each side of the equation. 5 + -2insx + 6insx = 9 + -6insx + 6insx Combine like terms: -2insx + 6insx = 4insx 5 + 4insx = 9 + -6insx + 6insx Combine like terms: -6insx + 6insx = 0 5 + 4insx = 9 + 0 5 + 4insx = 9 Add '-5' to each side of the equation. 5 + -5 + 4insx = 9 + -5 Combine like terms: 5 + -5 = 0 0 + 4insx = 9 + -5 4insx = 9 + -5 Combine like terms: 9 + -5 = 4 4insx = 4 Divide each side by '4nsx'. i = n-1s-1x-1 Simplifying i = n-1s-1x-1
| 0.05x^2-0.1=0 | | 4r-12=15 | | 5+0.8a=14.6 | | W=3*2+4*6 | | 2w^2+21w+52=0 | | 2(x-5)+x=71 | | 11y-7z+8x+2y+9z-5x= | | 2(k-9)=-18 | | 2w^2+21w+52=69 | | 9y-8b=13.83 | | 26-2t=-12 | | 5+0.8=14.6 | | 4y-10x=-8 | | 0.0476x^2-0.1=0 | | 3x-4x+20=24 | | 8(5x-5)-4=2(6-8x) | | 6.99-0.55=11.95 | | -q=21 | | y=4x^2-13 | | 2x+10=x+26 | | 84h-65h-15h+4=56 | | 4(2x-7)=16 | | 27+4w=5w | | 67-x=76-2x | | 7n-6=-146 | | -88=2(g+42) | | 6x^19=0 | | 8=67-k | | 4y-4x=-8 | | 6=20(0.9)x | | x^2-80x-500=0 | | 6x+y=78 |